Corporal punishment and gender equality: regimes of care and rights in South African schools. Issue 3 (3rd April 2021) - Hunter, Mark; Morrell, Robert
ABSTRACT: Many policy interventions designed to achieve gender equality in education are predicated on the assumption that the enforcement of a human rights framework will promote equality and reduce (gender) inequalities. In South Africa, the ending of apartheid led to the introduction of a rights-based constitution in 1996. In line with this Constitution the education system was overhauled and a new Act, the South African Education Act of 1996 came into force. Despite one of the most progressive constitutions in the world and the authority of the Education Act, progress has been limited towards reducing gender inequality and gender-based violence. In this paper we focus on the continuing illegal use of corporal punishment (CP) to explore the limitations of a right-based approach to gender transformation in schools. Drawing on research undertaken in schools of vastly different socio-economic status we argue that rights-based approaches against CP resonate most in middle-class schools that have close links to formal work. In contrast, in other schools, certain types of CP have persisted often with the approval of parents and learners where they are thought of as a caring and necessary means to redress schooling inequities.